2016
DOI: 10.15171/apb.2016.046
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Nanosuspensions as Potential Ophthalmic Delivery Systems for Ketotifen Fumarate

Abstract: IntroductionEye is the most exclusive organ of the body and a wide range of drug delivery systems are employed to deliver the drug into the eye. Presently, conventional eye drops encompass more than 90% of the marketed ophthalmic formulations. However, after using an eye drop, normally up to 5% of the instilled drug passes the cornea and reaches the intraocular tissues. This happens because of quick and vast precorneal drop loss afforded by blinking and high tear fluid output. To this end, controlled drug deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Doxorubicin/sodium bicarbonate (DOX/NaHCO 3 ) nanosuspensions were prepared by the solvent diffusion method, which was mentioned in the previous study . First, EC and TWEEN 80 were dissolved in acetonitrile.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Doxorubicin/sodium bicarbonate (DOX/NaHCO 3 ) nanosuspensions were prepared by the solvent diffusion method, which was mentioned in the previous study . First, EC and TWEEN 80 were dissolved in acetonitrile.…”
Section: Methodsmentioning
confidence: 99%
“…Doxorubicin/sodium bicarbonate (DOX/ NaHCO 3 ) nanosuspensions were prepared by the solvent diffusion method, which was mentioned in the previous study. 23 First, EC and TWEEN 80 were dissolved in acetonitrile. Second, DOX chloroform solution and NaHCO 3 aqueous solution were sequentially injected into acetonitrile under rapid stirring.…”
Section: Methodsmentioning
confidence: 99%
“…The intraocular pressure on the rabbit eye was assessed, for a period up to 12 h, after instillation of the given formulations in the previous referred structure. The results showed that all suspensions presented higher area under the curve (AUC) values in comparison to solutions of drugs with the drugs formulated in nanosuspensions determined to have extensive absorption and increased therapeutic effect in relation to drug solutions [171,175]. Other research carried out by Ali and collaborators related the variable bioavailability of hydrocortisone nanosuspensions formulated using precipitation methodologies with the same parameter on hydrocortisone solutions settled with milling apparatus.…”
Section: Drug Delivery Systems For Ocular Routementioning
confidence: 99%
“…In addition to the prolonged and controlled release of drug, another advantage of these systems for ocular drug delivery is the increase in time the drug is retained in the cul-de-sac without increasing tonicity. [37][38][39][40][41] In a 2016 study, nanosuspensions containing econazole were prepared using methyl-β-cyclodextrin and hydroxylpropyl-β-cyclodextrin and various stabilizers, such as polyethylene oxide, polyvinyl pyrrolidone k30, poloxamer 407, Tween 80, and Cremophor EL, with the nano-spray dryer technique. To prepare the nanosuspension formulation, nanoparticles were suspended in isotonic buffer and chitosan-hydrochloric acid solution.…”
Section: Nanosuspensionsmentioning
confidence: 99%
“…In addition to the prolonged and controlled release of drug, another advantage of these systems for ocular drug delivery is the increase in time the drug is retained in the cul-de-sac without increasing tonicity. 37 - 41 …”
Section: Novel Drug Delivery Systemsmentioning
confidence: 99%